Effects of a 12-Week Structured Badminton Training Program on Agility, Psychological Confidence, and Body Composition Among Obese Junior High School Students: A Quasi-Experimental Study - Hao, Chen; Mitranun , Witid (Journal for Developing the Social and Community, 2025)
Background and Aim: Adolescent obesity significantly impacts both physical health and psychological well-being, often leading to reduced agility, impaired self-confidence, and limited engagement in physical activities. Based on self-efficacy and self-esteem theories, this study aimed to investigate the impact of a structured badminton training program on agility, psychological confidence, and body composition in obese junior high school students. Materials and Methods: Forty obese students aged 12–14 years were recruited and randomly assigned to either an experimental group (n = 20) or a control group (n = 20). The experimental group participated in a structured 12-week badminton training program, conducted three times per week, incorporating agility-focused exercises and progressive skill training, while the control group continued routine school activities without additional interventions. Agility was measured using T-shaped run and cross-quadrant jump tests; psychological confidence was assessed via a standardized psychological confidence scale; body composition indicators included BMI, body fat percentage, and waist-to-hip ratio. Data analysis employed paired-sample and independent-sample t-tests. Results: The experimental group showed significant improvements in agility, psychological confidence, and body composition compared to the control group (p<0.01). Specifically, the intervention notably enhanced agility performance, psychological confidence, and resulted in positive changes in body composition measures. Conclusion: The structured badminton training significantly improved agility, psychological confidence, and body composition among obese adolescents, supporting the applicability of self-efficacy and self-esteem frameworks. This study emphasizes the value of integrating theoretically informed, structured physical training into school curricula to address adolescent obesity holistically.